2015
DOI: 10.1109/twc.2014.2375874
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Multi-Point Transmission With Imperfect CSI and Other-Cell Interference

Abstract: International audienceCoordinated Multi-Point (CoMP) transmission for LTE-Advanced systems promises enhanced throughput and coverage performance, especially for cell edge users. However, the performance of CoMP systems heavily depends on the feedback quality and channel imperfections. In this paper, we investigate the impact of quantized and delayed channel state information (CSI) on the average achievable rate of joint transmission (JT) and coordinated beamforming (CBF) systems. We derive closed-form expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 25 publications
0
33
0
1
Order By: Relevance
“…ASE for JT CoMP with discrete-rate adaptation with different quantized modulation schemes (BERtar = 10 −3 , γ j = 4.5 dB, and γ k = 5.5 dB). into (7) and using integration by parts to simplify the terms to be integrated. Whenγ j =γ k =γ η ave,3 =…”
Section: Appendix Bmentioning
confidence: 99%
See 1 more Smart Citation
“…ASE for JT CoMP with discrete-rate adaptation with different quantized modulation schemes (BERtar = 10 −3 , γ j = 4.5 dB, and γ k = 5.5 dB). into (7) and using integration by parts to simplify the terms to be integrated. Whenγ j =γ k =γ η ave,3 =…”
Section: Appendix Bmentioning
confidence: 99%
“…In [6], the performance of CoMP when orthogonal beamforming is utilized was focused on. Finally, in [7], the impact that quantized (and delayed) channel state information (CSI) has on the average data rate that JT and coordinated beamforming CoMP can achieve was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The latter modeling of the OCI's vector elements was used in the analysis of [5], where it was considered that OCI is made up of a large number of interference terms, and thus can be effectively approximated as Gaussian. For general values of m ≥ 0.5 in (5), the adopted model resembles that of [7], [14], [15], where the amplitude distribution of each element of g b , computed using both the hexagonal grid and stochastic geometry models, was approximated by a Gamma RV through the moment matching approach. Starting from (1) and considering the OCI model of (5), it can be easily concluded that the received power of the desired signal at MT b with channel estimation and that of its received aggregate OCI are related as in the left-hand side of (4), yielding…”
Section: A System Model Incorporating Oci and Csi Imperfectionsmentioning
confidence: 99%
“…These designs try to limit the JP cluster sizes and, thus, implicitly reduce the backhaul overhead. The impact of partial or imperfect CSI feedback to CB and JP has been studied, e.g., in [10]. Pilot contamination in TDD based transceiver training for coordinated beamforming has been considered in [11].…”
mentioning
confidence: 99%